Optical diffusion film with high light transmittance and high haze and preparation method thereof

By using specific matrix materials and surface modified monodispersed calcium carbonate particles, the problem that light diffusion properties and transmittance of the light diffusion film are difficult to simultaneously improve, and an optical diffusion film with high light transmittance and high haze is achieved, which reduces production costs.

CN119708719AActive Publication Date: 2025-03-28GUILIN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411920808.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

When the conventional light diffusion film improves light diffusion properties (haze), the light transmittance tends to decrease, or when the light transmittance is increased, the light diffusion properties (haze) are poor, making it difficult to improve simultaneously.

Method used

One or more of polystyrene, polycarbonate or polyethylene terephthalate are used as the matrix material, and calcium carbonate particles in the monodispersed state are combined as the light diffusing agent, and the proportion and grain size of the material in the optical diffusing film are controlled through surface modification to achieve high light transmittance and high haze.

Benefits of technology

The optical diffusion film has achieved a light transmittance and haze of more than 85%, solving the technical problem that light diffusion and transmittance are difficult to simultaneously improve, and at the same time reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207928370000091
    Figure BDA0005207928370000091
  • Figure BDA0005207928370000101
    Figure BDA0005207928370000101
  • Figure HDA0005207928380000011
    Figure HDA0005207928380000011
Patent Text Reader

Abstract

The invention discloses an optical diffusion film with high light transmittance and high haze. The optical diffusion film comprises the following raw materials in percentage by mass: 88.5%-97.5% of a base material, 2%-10% of a light diffusion agent and 0.5%-1.5% of an antioxidant, wherein the base material is one or more of polystyrene, polycarbonate or polyethylene glycol terephthalate; the light diffusant is calcium carbonate particles in a monodisperse state, the grain size is mainly concentrated in a range of 800-1200 nm, and the proportion exceeding the range is lower than 10%. The preparation method comprises the following steps: stirring and blending a light diffusion agent with a small amount of a base material and a small amount of an antioxidant, and carrying out extrusion granulation to obtain filler master batch; and uniformly stirring and mixing the filler master batch with the balance of the base material and the antioxidant, and carrying out film / sheet casting or extrusion film / sheet forming to obtain the high-light-transmittance and high-haze optical diffusion film. The light transmittance and the haze of the optical diffusion film both exceed 85%, and the technical problem that the light diffusivity and the transmittance of the optical diffusion film are difficult to improve at the same time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optics, and in particular relates to an optical diffusion film with high light transmittance and high haze and a preparation method thereof. Background Art

[0002] In the field of optical display and lighting, light diffusion films / sheets are generally needed to achieve light diffusion of "point light sources" such as LEDs, thereby forming "surface light sources". The commonly used method at present is to use a faceted light guide plate + light diffusion film, in which the light diffusion film uses polystyrene, polymethyl methacrylate or polyethylene terephthalate as the base material, and silicon microspheres or polyester microspheres are added to the film or on the surface. Light diffusion is achieved through the light scattering (refraction + reflection) of the microspheres. However, this method has a contradiction between light diffusion (i.e., haze) and transmittance, that is, if the light diffusion is good (high haze), the transmittance is low, and if the transmittance is good, the light diffusion is poor (low haze). Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide an optical diffusion film with high light transmittance and high haze in view of the deficiencies of the above-mentioned prior art. The light transmittance and haze are both greater than 85%, solving the technical problem that it is difficult to simultaneously improve the light diffusion property and transmittance of the light diffusion film.

[0004] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0005] An optical diffusion film with high light transmittance and high haze, the raw materials of which include, by mass percentage, 88.5% to 97.5% of a base material, 2% to 10% of a light diffuser, and 0.5% to 1.5% of an antioxidant; wherein the base material is one or more of polystyrene (PS), polycarbonate (PC) or polyethylene terephthalate (PET), and the light diffuser is monodisperse calcium carbonate particles.

[0006] According to the above scheme, PS is highly transparent optical grade PS, usually called GPPS, with a number average molecular weight between 30,000 and 120,000; PC is highly transmittance, high diffusion, no glare, no light and shadow optical grade PC, with a number average molecular weight between 10,000 and 20,000; PET is highly transmittance film grade PET, with a number average molecular weight between 15,000 and 30,000.

[0007] According to the above scheme, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, antioxidant 626, antioxidant S-9228 and the like.

[0008] The method for preparing the optical diffusion film with high light transmittance and high haze specifically comprises the following steps:

[0009] (1) According to the mass percentage, 88.5% to 97.5% of the base material, 2% to 10% of the light diffuser, and 0.5% to 1.5% of the antioxidant are weighed; 88.5% to 97.5% of the base material is divided into two parts A and B, including 0.5% to 6.5% of the base material A and 82% to 97% of the base material B; 0.5% to 1.5% of the antioxidant is divided into two parts A and B, including 0.05% to 0.15% of the antioxidant A and 0.45% to 1.35% of the antioxidant B; wherein the mass percentages of the base material A, the base material B, the antioxidant A, and the antioxidant B are all calculated based on their proportion in the total amount of the raw materials;

[0010] (2) blending the light diffuser, the base material A and the antioxidant A by a stirrer at room temperature, and extruding and granulating the mixture by a twin-rotor continuous mixing extruder to obtain a filler masterbatch; wherein the mass percentage of calcium carbonate in the filler masterbatch is 60% to 80%;

[0011] (3) The filler masterbatch, the matrix material B and the antioxidant B are uniformly mixed with a stirrer at room temperature, and then cast into a film / sheet or extruded into a film / sheet; the cast or extruded film / sheet is cut to obtain an optical diffusion film with high light transmittance and high haze.

[0012] According to the above scheme, in step (2), the filler masterbatch is preferably in the shape of short rods with a diameter of 2 to 3 mm and a length of 1 to 3 mm.

[0013] According to the above scheme, in step (2), the extrusion temperature is generally in the range of 175-250°C, and the screw speed is adjusted between 300-700 rpm according to the material state. Specifically, when the base material is PS, the extruder temperature is set at 175-180°C; when the base material is PC, the extruder temperature is set at 245-250°C; when the base material is PET, the extruder temperature is set at 235-240°C.

[0014] According to the above scheme, in step (3), when the base material is PS, the temperature of casting or extrusion is set at 190-240°C; when the base material is PC, the temperature of casting or extrusion is set at 250-280°C; when the base material is PET, the temperature of casting or extrusion is set at 240-270°C.

[0015] According to the above scheme, in step (3), the thickness of the film / sheet may vary depending on the application field and the substrate material, and is generally between 0.1 and 3 mm.

[0016] According to the above scheme, the grain size of the monodisperse calcium carbonate particles is mainly concentrated in 800-1200nm, the particles outside this range are less than 10%, the particles larger than 1.5μm are less than 2%, and the grains are well crystallized. The preparation method of the monodisperse calcium carbonate particles comprises the following steps:

[0017] S1. Prepare calcium carbonate slurry by calcination, digestion, carbonization and other processes; wherein, the calcination process is: select limestone with uniform grain size as raw material (the grain size is preferably 0.05-5mm), adopt calcination temperature matching the grain size (according to the grain size from small to large, the calcination temperature is preferably from 850-1000℃), and obtain quicklime; the digestion process is: digest quicklime and hot water at 80-90℃, and obtain lime milk (raw slurry) after aging; carbonization: adjust the solid content of lime milk to 5%-15%, and then introduce carbon dioxide for carbonization, the carbonization starting temperature is 45-70℃, CO 2 The content is 20% to 40%, and the slurry is carbonized until the pH value is 8.0 to 10.0, and then the carbonization is terminated to obtain the calcium carbonate cooked slurry;

[0018] S2. The calcium carbonate slurry obtained in S1 is allowed to stand and the supernatant is removed to achieve concentration, thereby obtaining a calcium carbonate slurry having a solid content of 20% to 40%;

[0019] S3. Add the inorganic crystal reconstruction agent and the organic crystal reconstruction agent to the calcium carbonate slurry obtained in S2, and stir under ultrasonic conditions (power density 100-300W / 1000cm 3 ) at 140-200° C. for 1.5-4 h for dispersion and reconstruction to obtain a monodisperse calcium carbonate suspension with a specified particle size and morphology;

[0020] S4. The monodisperse calcium carbonate suspension obtained in S3 is cooled to 50 to 70°C, a surface modifier is added, and the temperature is maintained within the range and stirred for 20 to 40 min to obtain a surface-modified calcium carbonate suspension;

[0021] S5. The surface-modified calcium carbonate suspension obtained in S4 is dehydrated by filter pressing to obtain a calcium carbonate filter cake, wherein the moisture content of the filter cake is controlled to be no more than 40%;

[0022] S6. Dry the calcium carbonate filter cake obtained in S5 by belt drying and flash evaporation to control the moisture content below 0.1% to obtain monodisperse calcium carbonate particles, the activation degree of which is required to be higher than 99%, and the activation degree is tested according to the national standard GB / T 19281-2014.

[0023] Furthermore, the inorganic crystal reconstructor is selected from one or more of sodium silicate, sodium chloride, aluminum chloride, zinc sulfate, etc.; the organic crystal reconstructor is selected from one or more of ethanol, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, disodium ethylenediaminetetraacetate, etc.; the total amount of the inorganic crystal reconstructor and the organic crystal reconstructor is 0.5% to 5% of the dry mass of calcium carbonate.

[0024] Furthermore, the surface modifier is a mixture of amphiphilic polystyrene-polyethylene glycol block copolymer and polyethylene glycol stearate or pentaerythritol stearate, and the amount is 2% to 5% of the dry mass of calcium carbonate. When the base material is PS, the surface modifier is composed of amphiphilic polystyrene-polyethylene glycol block copolymer and polyethylene glycol stearate in a mass ratio of 1:1 to 1:2; when the base material is PC, the surface modifier is composed of amphiphilic polystyrene-polyethylene glycol block copolymer and pentaerythritol stearate in a mass ratio of 1:2 to 1:4; when the base material is PET, the surface modifier is composed of amphiphilic polystyrene-polyethylene glycol block copolymer and pentaerythritol stearate in a mass ratio of 1:4 to 1:6. Wherein, the molecular weight of the amphiphilic polystyrene-polyethylene glycol block copolymer is between 40,000 and 120,000 g / mol.

[0025] The technical concept of the present invention is as follows:

[0026] The present invention uses polystyrene, polycarbonate or polyethylene terephthalate as the matrix material. The refractive index of these materials is close to that of calcium carbonate, which can reduce the total reflection caused by the refractive index difference at the interface of calcium carbonate @ matrix; at the same time, the present invention uses calcium carbonate particles with a grain size concentrated in 800-1200nm and good crystallization in a monodispersed state as a light diffuser, which is dispersed in the matrix material to form a diffusion effect on visible light. Moreover, during the preparation process of the light diffuser, the calcium carbonate is surface treated, which can be well dispersed in the matrix material and well bonded to the interface of the matrix material to avoid sudden changes in refractive index due to interface gaps. The present invention further controls the mass percentage of the matrix material in the optical diffusion film to 88.5%-97.5%, the mass percentage of the light diffuser to 2%-10%, and the mass percentage of the antioxidant to 0.5%-1.5%, and finally achieves that the light transmittance and haze of the optical diffusion film are both over 85%.

[0027] Among them, when preparing a light diffuser (monodisperse calcium carbonate particles), the present invention selects limestone with uniform grain size as a raw material, adopts a calcination temperature that matches the grain size, obtains quicklime with moderate and uniform activity, and then carbonizes it after digestion to obtain calcium carbonate slurry. In this process, the limestone with uniform grain size is adjusted for lime activity through the limestone calcination process to avoid partial raw burning and partial overburning caused by porphyritic grains; then, lime with good uniformity and moderate activity is conducive to the control of the digestion reaction, and uniform lime milk with controllable properties is obtained, thereby realizing the control of the later carbonization process, thereby obtaining calcium carbonate slurry. The calcium carbonate slurry undergoes a process step of reconstructing the grain surface after thickening. By adding an inorganic surface reconstructor and an organic surface reconstructor and keeping it warm at a certain temperature, the grain surface reconstruction is promoted, the crystals are more complete, the particle surface is smoother, and the surface energy is reduced, which is conducive to dispersion. Among them, the role of inorganic surface reconstruction agents is to promote crystal development, repair defects, and make crystals more complete; the role of organic surface reconstruction agents is to adjust the surface potential of particles, control the mutual repulsion of grains in water, and avoid adhesion during crystal repair. The present invention controls the average particle size of calcium carbonate particles to 800-1200nm by controlling the temperature and time of grain surface reconstruction, and then dries after surface modification to ensure that the obtained calcium carbonate powder is in a highly monodisperse state. The particle size of calcium carbonate particles in this form is within the visible light wavelength range. The birefringence of calcium carbonate is used to decompose the visible light passing through calcium carbonate into two beams of polarized light with different speeds and propagation directions. After passing through n calcium carbonate particles, 2n beams of light with different propagation directions are decomposed. The size and interface of the calcium carbonate grains are controlled to reduce reflection, thereby achieving the functions of high light transmittance and high haze at the same time.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The light transmittance and haze of the optical diffusion film of the present invention are both over 85%, which solves the technical problem that it is difficult to simultaneously improve the light diffusion property and transmittance of the optical diffusion film, and the production cost is also significantly lower than that of existing products. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope photo of the light diffusing agent prepared in Example 1;

[0031] Figure 2 This is a scanning electron microscope photo of the light diffusing agent prepared in Example 2;

[0032] Figure 3 This is a scanning electron microscope photograph of the light diffusing agent prepared in Example 3;

[0033] Figure 4 This is a scanning electron microscope photograph of the light diffusing agent prepared in Example 4;

[0034] Figure 5 This is a scanning electron microscope photo of the calcium carbonate prepared in Comparative Example 1;

[0035] Figure 6 This is a scanning electron microscope photo of the calcium carbonate prepared in Comparative Example 2;

[0036] Figure 7 This is a scanning electron microscope photo of the calcium carbonate prepared in Comparative Example 3;

[0037] Figure 8 This is a scanning electron microscope photograph of calcium carbonate prepared in Comparative Example 4. Specific implementation methods

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] In the following examples, PS was purchased from Formosa Chemicals & Plastics (Ningbo) Co., Ltd., model GP550N; PC was purchased from Idemitsu Kosan Co., Ltd., model LC1500; PET was purchased from Sinopec Yizheng Chemical Fiber Co., Ltd., model FG720; antioxidant 1010, antioxidant 168 and antioxidant 626 were purchased from BASF; antioxidant S-9228 was purchased from Dover Corporation, USA.

[0040] In the following examples, the CAS number of the polyethylene glycol stearate is 9004-99-3, and the CAS number of the pentaerythritol stearate is 115-83-3.

[0041] In the following examples, the amphiphilic polystyrene-polyethylene glycol block copolymer (PS-b-PEG) was prepared by atom transfer radical polymerization (ATRP), firstly using styrene (St) as a monomer and CBr 4 As a telogen, azobisisobutyronitrile (AIBN) as an initiator, a free radical telomerization reaction was used to synthesize polystyrene (PS-Br) telomers, wherein the polymerization degree of PS-Br was 300 to 1000. Then, ethylene glycol (EG) was used as a monomer, PS-Br was used as a macromolecular initiator, and CuCl / pby was used as a catalyst system to synthesize a block copolymer PS-b-PEG by ATRP method, wherein the molar ratio of EG, PS-Br, CuCl and pby was 100:1:2:6, the reaction temperature was 90 to 130°C, and the reaction time was 4 to 24h.

[0042] Example 1

[0043] An optical diffusion film with high light transmittance and high haze, whose raw materials include, by mass percentage: 91% of base material, 8% of light diffuser, and 1% of antioxidant; wherein, the base material is PS, the light diffuser is monodispersed calcium carbonate particles, and the antioxidant is antioxidant 168.

[0044] The method for preparing the optical diffusion film with high light transmittance and high haze specifically comprises the following steps:

[0045] (1) According to the above mass percentages and raw material specifications, 91% of the base material, 8% of the light diffuser, and 1% of the antioxidant are weighed; then, the base material is divided into two parts, marked as base material A and base material B; wherein the mass percentage of the base material A is 3%, the mass percentage of the base material B is 88%, and the sum of the two is 91%; and the antioxidant is divided into two parts, marked as antioxidant A and antioxidant B, wherein the mass percentage of the antioxidant A is 0.1%, the mass percentage of the antioxidant B is 0.9%, and the sum of the two is 1%;

[0046] (2) The light diffuser, the base material A and the antioxidant A are mixed with a stirrer at room temperature, and extruded into granules through a twin-rotor continuous mixing extruder. The temperatures of the various sections of the extruder (i.e., the feeding section, the compression section and the homogenizing section) are set to 175° C., 180° C. and 180° C., and the screw speed is adjusted between 300 and 700 rpm according to the viscosity of the material during extrusion, with the ability to be extruded smoothly as the basis, to obtain a short rod-shaped filler masterbatch with a diameter of 2 to 3 mm and a length of 1 to 3 mm. At this time, the mass percentage of calcium carbonate in the filler masterbatch is about 72%;

[0047] (3) The filler masterbatch, the base material B and the antioxidant B are stirred and mixed uniformly in a mixer at room temperature, and then formed into a film by a casting machine. The temperatures of each section of the casting machine are set to 190°C, 220°C, 220°C, 200°C and 230°C. The winding speed of the casting roller is 1.0 m / min, the speed of the pulling roller is 1.1 m / min, the film thickness is 260 μm, and the optical diffusion film with high light transmittance and high haze is obtained after cutting.

[0048] The method for preparing the monodisperse calcium carbonate particle light diffuser comprises the following specific steps:

[0049] S1. Prepare calcium carbonate slurry by calcination, digestion and carbonization process. The calcination process is as follows: select high-purity limestone with a grain size of 0.2-0.5 mm as raw material, adopt calcination temperature of 900℃, calcine for 2 hours, and obtain quicklime with ideal activity; the digestion process is as follows: digest the quicklime obtained by calcination with water at 80℃ to obtain lime milk, and then age it for 48 hours and remove impurities to obtain lime milk (raw slurry); the carbonization process is as follows: add water to the lime milk to adjust the solid content to 15%, and then introduce carbon dioxide for carbonization, the carbonization starting temperature is 45℃, CO 2 The content is 40%, and the slurry is carbonized until the pH value reaches 8.0-8.5, and the carbonization is terminated to obtain the calcium carbonate cooked slurry;

[0050] S2. The calcium carbonate slurry obtained in S1 was allowed to stand and the supernatant was removed to achieve concentration, thereby obtaining a calcium carbonate slurry having a solid content of 20%;

[0051] S3. The calcium carbonate slurry obtained in S2 was added with 1.0% aluminum chloride, 0.5% polyvinyl pyrrolidone, 2.0% polyvinyl alcohol and 0.3% sodium lauryl sulfate on a dry basis of calcium carbonate at a power density of 300W / 1000cm 3 The mixture was dispersed and reconstructed at 200°C for 1.5 h under ultrasonic conditions to obtain a monodisperse calcium carbonate suspension.

[0052] S4. The monodisperse calcium carbonate suspension obtained in S3 was cooled to 70°C, 2% PS-b-PEG and 3% polyethylene glycol stearate were added on a dry basis of calcium carbonate, and the mixture was kept at 70°C and stirred for 20 min to complete the surface modification of the calcium carbonate to obtain a surface-modified calcium carbonate suspension;

[0053] S5. The surface-modified calcium carbonate suspension obtained in S4 is dehydrated by filter pressing to obtain a calcium carbonate filter cake having a moisture content of less than 40%;

[0054] S6. Dry the calcium carbonate filter cake obtained in S5 by belt drying or flash evaporation, etc., until the moisture content is less than 0.1%, and the calcium carbonate filter cake is monodispersed. Figure 1 As shown, the calcium carbonate particles are cubic in shape, with a particle size distribution concentrated in the range of 800-1200 nm, less than 10% of the particles are outside this range, less than 2% of the particles are larger than 1.5 μm, the interfaces between the particles are clear, the edges and corners are distinct, the dispersion is good, and the activation degree is tested to be 99.5%.

[0055] Example 2

[0056] This embodiment provides an optical diffusion film with high light transmittance and high haze, and its raw materials include, by mass percentage: 92.5% of base material, 7% of light diffuser, and 0.5% of antioxidant; wherein, the base material is PS, the light diffuser is monodisperse calcium carbonate particles, and the antioxidant is antioxidant 1010.

[0057] The method for preparing an optical diffusion film with high light transmittance and high haze described in this embodiment is different from that in Embodiment 1 in that: the mass percentage of base material A is 4.5%, the mass percentage of base material B is 88%; the mass percentage of antioxidant A is 0.05%, the mass percentage of antioxidant B is 0.45%; and the filling rate of calcium carbonate in the filler masterbatch is about 60%.

[0058] The preparation method of the monodisperse calcium carbonate particle light diffuser described in this embodiment is different from that in embodiment 1 in that: in step S1, the digestion temperature is 85°C, the solid content of the raw pulp used for carbonization is 10%, the carbonization starting temperature is 50°C, and the CO 2 In step S3, 0.5% sodium silicate, 0.2% sodium chloride, 0.6% aluminum chloride and 1.0% sodium dodecylbenzene sulfonate based on the dry weight of calcium carbonate are added as crystal reconstruction agents, and the ultrasonic power density is 280W / 1000cm 3 , the heat preservation temperature is 180℃, and the heat preservation time is 4h; in step S4, 1.5% PS-b-PEG and 1.5% polyethylene glycol stearate are added as modifiers based on the dry weight of calcium carbonate, and the mixture is stirred at 65℃ for 30min. The monodispersed calcium carbonate particles obtained are as follows Figure 2 As shown, the calcium carbonate particles are polyhedral, with a particle size distribution concentrated in the range of 800-1200 nm, less than 10% of the particles are outside this range, less than 2% of the particles are larger than 1.5 μm, the interfaces between the particles are clear, the dispersion is good, and the activation degree is 99.9%.

[0059] Example 3

[0060] This embodiment provides an optical diffusion film with high light transmittance and high haze, and its raw materials include, by mass percentage: 94% base material, 5% light diffuser, and 1% antioxidant; wherein, the base material is PET, the light diffuser is monodisperse calcium carbonate particles, and the antioxidant is antioxidant S-9228.

[0061] The method for preparing the optical diffusion film with high light transmittance and high haze described in this embodiment specifically comprises the following steps:

[0062] (1) According to the above mass percentages and raw material specifications, 94% of base material, 5% of light diffuser, and 1% of antioxidant are weighed; then, the base material is divided into two parts, marked as base material A and base material B; wherein the mass percentage of base material A is 2%, the mass percentage of base material B is 92%, and the sum of the two is 91%; and the antioxidant is divided into two parts, marked as antioxidant A and antioxidant B, wherein the mass percentage of antioxidant A is 0.1%, the mass percentage of antioxidant B is 0.9%, and the sum of the two is 1%;

[0063] (2) The light diffuser, the base material A and the antioxidant A are mixed with a stirrer at room temperature, and extruded into granules through a twin-rotor continuous mixing extruder. The temperatures of each section of the extruder are set to 235° C., 240° C. and 240° C. The screw speed is adjusted between 300 and 700 rpm according to the viscosity of the material during extrusion, and the material is extruded smoothly to obtain a short rod-shaped filler masterbatch with a diameter of 2 to 3 mm and a length of 1 to 3 mm. At this time, the mass percentage of calcium carbonate in the filler masterbatch is about 70%;

[0064] (3) The filler masterbatch, the base material B and the antioxidant B are stirred and mixed uniformly in a mixer at room temperature, and then formed into a film by a casting machine. The temperatures of each section of the casting machine are set to 240°C, 260°C, 260°C, 250°C and 270°C. The winding speed of the casting roller is 0.9 m / min, the speed of the pulling roller is 1.0 m / min, the film thickness is 300 μm, and the optical diffusion film with high light transmittance and high haze is obtained after cutting.

[0065] The preparation method of the monodisperse calcium carbonate particle light diffuser described in this embodiment is different from that in embodiment 1 in that: in step S1, high-purity limestone with a grain size of 2.0 to 5.0 mm is selected as the raw material, the calcination temperature is 1000° C., the solid content of the raw slurry used for carbonization is 12%, the carbonization starting temperature is 60° C., and the CO 2 In step S3, 1.2% of zinc sulfate, 0.8% of sodium silicate, 1.4% of polyethylene glycol and 1.6% of hexadecyltrimethylammonium bromide were added as crystal reconstruction agents based on the dry weight of calcium carbonate, and the ultrasonic power density was 250W / 1000cm 3 , the heat preservation temperature is 200℃, and the heat preservation time is 3h; in step S4, 0.5% PS-b-PEG and 2% pentaerythritol stearate are added as modifiers based on the dry weight of calcium carbonate, and the mixture is stirred at 50℃ for 40min. The monodispersed calcium carbonate particles obtained are as follows Figure 3 As shown, the calcium carbonate particles are cubic in shape, with a particle size distribution concentrated between 800 and 1200 nm, less than 10% of the particles are outside this range, less than 2% of the particles are larger than 1.5 μm, the interfaces between the particles are clear, the edges and corners are distinct, the dispersion is good, and the activation degree is 99.6%.

[0066] Example 4

[0067] This embodiment provides an optical diffusion film with high light transmittance and high haze, and its raw materials include, by mass percentage: 88.5% base material, 10% light diffuser, and 1.5% antioxidant; wherein, the base material is PC, the light diffuser is monodisperse calcium carbonate particles, and the antioxidant is antioxidant 626.

[0068] The method for preparing the optical diffusion film with high light transmittance and high haze described in this embodiment specifically comprises the following steps:

[0069] (1) According to the above mass percentages and raw material specifications, 88.5% of the base material, 10% of the light diffuser, and 1.5% of the antioxidant were weighed; then, the base material was divided into two parts, marked as base material A and base material B; wherein the mass percentage of base material A was 2.4%, the mass percentage of base material B was 86.6%, and the sum of the two was 89%; and the antioxidant was divided into two parts, marked as antioxidant A and antioxidant B, wherein the mass percentage of antioxidant A was 0.15%, the mass percentage of antioxidant B was 1.35%, and the sum of the two was 1.5%;

[0070] (2) The light diffuser, the base material A and the antioxidant A are mixed with a stirrer at room temperature, and extruded into granules through a twin-rotor continuous mixing extruder. The temperatures of each section of the extruder are set to 245° C., 250° C. and 250° C., and the screw speed is adjusted between 300 and 700 rpm according to the viscosity of the material during extrusion. The material is extruded smoothly to obtain a short rod-shaped filler masterbatch with a diameter of 2 to 3 mm and a length of 1 to 3 mm. At this time, the mass percentage of calcium carbonate in the filler masterbatch is about 80%;

[0071] (3) The filler masterbatch, the base material B and the antioxidant B are stirred and mixed uniformly in a mixer at room temperature, and then formed into a film by a casting machine. The temperatures of each section of the casting machine are set to 250°C, 270°C, 270°C, 250°C and 280°C. The winding speed of the casting roller is 3.0 m / min, the speed of the pulling roller is 3.1 m / min, the film thickness is 110 μm, and the optical diffusion film with high light transmittance and high haze is obtained after cutting.

[0072] The preparation steps of the monodisperse calcium carbonate particle light diffuser described in this embodiment are different from those in embodiment 1 in that: in step S1, high-purity limestone with a grain size of 0.05-0.2 mm is selected as the raw material, the calcination temperature is 850°C, the solid content of the raw slurry used for carbonization is 5%, the carbonization starting temperature is 70°C, and the CO 2The content is 20%, and the carbonization is terminated when the slurry pH reaches 9.0-9.5; in step S3, 0.2% sodium chloride, 0.1% ethanol and 0.2% disodium ethylenediaminetetraacetic acid are added as crystal reconstruction agents based on the dry weight of calcium carbonate, and the ultrasonic power density is 200W / 1000cm 3 , the heat preservation temperature is 140℃, and the heat preservation time is 4h; in step S4, 0.5% PS-b-PEG and 1.5% pentaerythritol stearate are added as modifiers based on the dry weight of calcium carbonate, and the mixture is stirred at 60℃ for 30min. The monodispersed calcium carbonate particles obtained are as follows Figure 4 As shown, the calcium carbonate particles are polyhedral, with a particle size distribution concentrated in the range of 800-1200 nm, less than 10% of the particles are outside this range, less than 2% of the particles are larger than 1.5 μm, the interfaces between the particles are clear, the edges and corners are distinct, the dispersion is good, and the activation degree is 99.5%.

[0073] Example 5

[0074] This embodiment provides an optical diffusion film with high light transmittance and high haze, and its raw materials include, by mass percentage: 97% base material, 2% light diffuser, and 1% antioxidant; wherein, the base material is PET, the light diffuser is monodisperse calcium carbonate particles, and the antioxidant is antioxidant S-9228.

[0075] The method for preparing an optical diffusion film with high light transmittance and high haze described in this embodiment is different from that in Embodiment 3 in that: the mass percentage of base material A is 0.5%, the mass percentage of base material B is 96.5%; the mass percentage of antioxidant A is 0.1%, the mass percentage of antioxidant B is 0.9%; and the filling rate of calcium carbonate in the filler masterbatch is about 80%.

[0076] The preparation method of the monodisperse calcium carbonate particle light diffuser described in this embodiment is the same as that in Example 3.

[0077] Comparative Example 1

[0078] The difference between Comparative Example 1 and Example 1 is that no crystal reconstructing agent is added during the preparation of the light diffusing agent, and the other steps are the same as those of Example 1. The microscopic morphology of the prepared light diffusing agent is as follows: Figure 5 As shown, the particles have a rough surface, aggregate in the shape of short columns, and have poor dispersion.

[0079] Comparative Example 2

[0080] The difference between Comparative Example 2 and Example 1 is that in the preparation process of the light diffusing agent, no ultrasonic treatment is performed after the crystal reconstructing agent is added, and the other steps are the same as those in Example 1. The microscopic morphology of the prepared light diffusing agent is as follows: Figure 6 As shown, the particle surface is smooth but seriously agglomerated and the dispersion is poor.

[0081] Comparative Example 3

[0082] The difference between Comparative Example 3 and Example 2 is that during the preparation of the light diffuser, the grain surface reconstructor is 0.5% sodium dodecylbenzene sulfonate and 2.0% sodium dodecyl sulfate on a dry basis of calcium carbonate, and the other steps are the same. The microscopic morphology of the prepared light diffuser is as follows: Figure 7 As shown, the particle surface is rough, the particles are aggregated irregularly, and the dispersion is poor.

[0083] Comparative Example 4

[0084] The difference between Comparative Example 4 and Example 2 is that during the preparation of the light diffuser, the grain surface reconstructor is 0.5% sodium silicate and 1.5% aluminum chloride on a dry basis of calcium carbonate, and the other steps are the same. The microscopic morphology of the prepared light diffuser is as follows: Figure 8 As shown, the particle surface is smooth but the particles are bonded to each other, and the particles are aggregated in the form of short columns and nearly spherical particles, with poor dispersion.

[0085] Comparative Example 5

[0086] The difference between Comparative Example 5 and Example 4 is that in the preparation process of the light diffuser, the surface modifier is a stearic acid saponification liquid commonly used in the existing production technology. The preparation steps of the stearic acid saponification liquid are as follows: sodium hydroxide (the amount is 10% of the weight of stearic acid) and water (the amount is 9 times the weight of stearic acid) are placed in a saponification tank, and the temperature is raised to 75-80°C while stirring and dissolving. After all the sodium hydroxide is completely dissolved and the solution temperature reaches the target value, commercially available stearic acid is added to the saponification tank, maintained at 75-80°C, and stirred until the saponification reaction is completed. The other steps of Comparative Example 5 are the same as those of Example 4.

[0087] The performance test results of the optical diffusion film products prepared in the above examples and comparative examples are shown in Table 1. The transmittance and haze are tested according to the national standard GB / T 2410-2008. The present invention adopts the haze meter method, and the instrument used is BYK transmission haze meter, model AT4775.

[0088] Table 1 Performance test results

[0089]

[0090]

[0091] As can be seen from Table 1, although pure PS film, pure PET film, and pure PC film have a transmittance of more than 90%, the haze is less than 2%, which meets the basic characteristics of pure films; while the light diffusion film prepared by the present invention has a transmittance and haze of more than 85%. The comparative example has problems such as poor dispersibility and poor crystallinity of the calcium carbonate used, resulting in uneven diffusion films prepared, white spots, uneven dispersion of the diffusing agent, and white film defects, so the transmittance and haze are far lower than 85%. The present invention strictly controls the size and dispersibility of calcium carbonate grains, as well as the interface between calcium carbonate and the matrix material, reduces reflection, and thus simultaneously achieves the functions of high transmittance and high haze.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. An optical diffusion film with high light transmittance and high haze, characterized in that: The raw materials include, by mass percentage: 88.5% to 97.5% of base material, 2% to 10% of light diffuser, and 0.5% to 1.5% of antioxidant; wherein the base material is one or more of polystyrene, polycarbonate or polyethylene terephthalate; the light diffuser is monodisperse calcium carbonate particles, the grain size of which is mainly concentrated in the range of 800 to 1200 nm, and the proportion outside this range is less than 10%.

2. The optical diffusion film with high light transmittance and high haze according to claim 1, characterized in that: The polystyrene is of optical grade, with a number average molecular weight between 30,000 and 120,000; the polycarbonate is of optical grade, with a number average molecular weight between 10,000 and 20,000; the polyethylene terephthalate is film grade PET, with a number average molecular weight between 15,000 and 30,000; the antioxidant is selected from one or more of antioxidant 1010, antioxidant 168, antioxidant 626, antioxidant S-9228, etc.

3. The method for preparing an optical diffusion film with high light transmittance and high haze according to claim 1, characterized in that: The specific steps include: (1) According to the mass percentage, 88.5% to 97.5% of the base material, 2% to 10% of the light diffuser, and 0.5% to 1.5% of the antioxidant are weighed; 88.5% to 97.5% of the base material is divided into two parts A and B, including 0.5% to 6.5% of the base material A and 82% to 97% of the base material B; 0.5% to 1.5% of the antioxidant is divided into two parts A and B, including 0.05% to 0.15% of the antioxidant A and 0.45% to 1.35% of the antioxidant B; wherein the mass percentages of the base material A, the base material B, the antioxidant A, and the antioxidant B are all calculated based on their proportion in the total amount of the raw materials; (2) blending the light diffuser, the base material A and the antioxidant A by a stirrer at room temperature, and extruding and granulating the mixture by a twin-rotor continuous mixing extruder to obtain a filler masterbatch; wherein the mass percentage of calcium carbonate in the filler masterbatch is 60% to 80%; (3) The filler masterbatch, the matrix material B and the antioxidant B are uniformly mixed with a stirrer at room temperature, and then cast into a film / sheet or extruded into a film / sheet; the cast or extruded film / sheet is cut to obtain an optical diffusion film with high light transmittance and high haze.

4. The method for preparing an optical diffusion film with high light transmittance and high haze according to claim 3, characterized in that: In step (2), the extrusion temperature is in the range of 175 to 250° C., and the screw speed is adjusted between 300 and 700 rpm according to the material state; the filler masterbatch is in the shape of short rods with a diameter of 2 to 3 mm and a length of 1 to 3 mm.

5. The method for preparing an optical diffusion film with high light transmittance and high haze according to claim 4, characterized in that: When the base material is polystyrene, the extrusion temperature is set at 175-180°C; when the base material is polycarbonate, the extrusion temperature is set at 245-250°C; when the base material is polyethylene terephthalate, the extrusion temperature is set at 235-240°C.

6. The method for preparing an optical diffusion film with high light transmittance and high haze according to claim 3, characterized in that: In step (3), when the base material is polystyrene, the temperature of casting or extrusion is set at 190-240°C; when the base material is polycarbonate, the temperature of casting or extrusion is set at 250-280°C; when the base material is polyethylene terephthalate, the temperature of casting or extrusion is set at 240-270°C; the thickness of the film / sheet is between 0.1 and 3 mm.

7. The method for preparing an optical diffusion film with high light transmittance and high haze according to claim 3, characterized in that: The grain size of the monodisperse calcium carbonate particles is mainly concentrated in the range of 800-1200 nm, the proportion of particles exceeding this range is less than 10%, the proportion of particles larger than 1.5 μm is less than 2%, and the grains are well crystallized.

8. The method for preparing an optical diffusion film with high light transmittance and high haze according to claim 3, characterized in that: The method for preparing the monodisperse calcium carbonate particles comprises the following steps: S1. Prepare calcium carbonate slurry by calcination, digestion, carbonization and other processes; wherein, the calcination process is: select limestone with uniform grain size as raw material, calcine to obtain quicklime; the digestion process is: digest quicklime and hot water at 80-90°C, and obtain lime milk after aging; carbonization: adjust the solid content of lime milk to 5%-15%, introduce carbon dioxide for carbonization, the carbonization starting temperature is 45-70°C, CO2 content is 20%-40%, carbonize until the slurry pH is 8.0-10.0, end carbonization, and obtain calcium carbonate slurry; S2. The calcium carbonate slurry obtained in S1 is allowed to stand and the supernatant is removed to achieve concentration, thereby obtaining a calcium carbonate slurry having a solid content of 20% to 40%; S3. Add the inorganic crystal reconstruction agent and the organic crystal reconstruction agent to the calcium carbonate slurry obtained in S2 at a power density of 100 to 300 W / 1000 cm 3 The mixture is dispersed and reconstructed at 140-200°C for 1.5-4 hours under ultrasonic conditions to obtain a monodisperse calcium carbonate suspension. S4. The monodisperse calcium carbonate suspension obtained in S3 is cooled to 50 to 70 ° C, a surface modifier is added, and the mixture is kept warm and stirred to obtain a surface-modified calcium carbonate suspension; S5. The surface-modified calcium carbonate suspension obtained in S4 is dehydrated by filter pressing to obtain a calcium carbonate filter cake, wherein the moisture content of the filter cake is controlled to be no more than 40%; S6. Drying the calcium carbonate filter cake obtained in S5 until the moisture content is less than 0.1% to obtain monodisperse calcium carbonate particles with an activation degree of more than 99%.

9. The method for preparing an optical diffusion film with high light transmittance and high haze according to claim 8, characterized in that: The inorganic crystal reconstruction agent is selected from one or more of sodium silicate, sodium chloride, aluminum chloride, and zinc sulfate; the organic crystal reconstruction agent is selected from one or more of ethanol, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, and disodium ethylenediaminetetraacetate; the total amount of the inorganic crystal reconstruction agent and the organic crystal reconstruction agent is 0.5% to 5% of the dry mass of calcium carbonate.

10. The method for preparing an optical diffusion film with high light transmittance and high haze according to claim 3, characterized in that: The surface modifier is a mixture of amphiphilic polystyrene-polyethylene glycol block copolymer and polyethylene glycol stearate or pentaerythritol stearate, and the dosage is 2% to 5% of the dry basis weight of calcium carbonate; when the base material is polystyrene, the surface modifier is composed of amphiphilic polystyrene-polyethylene glycol block copolymer and polyethylene glycol stearate in a mass ratio of 1:1 to 1:2; when the base material is polycarbonate, the surface modifier is composed of amphiphilic polystyrene-polyethylene glycol block copolymer and pentaerythritol stearate in a mass ratio of 1:2 to 1:4; when the base material is polyethylene terephthalate, the surface modifier is composed of amphiphilic polystyrene-polyethylene glycol block copolymer and pentaerythritol stearate in a mass ratio of 1:4 to 1:6.

Citation Information

Patent Citations

  • Light diffusion agent mother material used for light diffusion film, preparation method and application thereof

    CN101812220A

  • Light diffusion master batch, PET film and preparation method thereof

    CN108276750A

  • Light-diffusing film and production method therefor, and display device

    CN109313288A

  • Optical diffusion polyester master batch, optical diffusion polyester film and preparation methods of optical diffusion polyester master batch and optical diffusion polyester film

    CN113820761A

  • Preparation method of large and small cubic dispersed precipitated calcium carbonate

    CN114291835A

Cited By

  • High-transmittance high-haze light diffusion resin / PET alloy material, preparation method and LED floor tile screen mask

    CN120442028A